Bi and oxygen defects improved visible light photocatalysis with BiOBr nanosheets. (24th September 2020) - Ren, Xiaozhen; Zhang, Xunshuang; Guo, Ruichen; Zhang, Shulan; Wang, Lezhi; Pu, Xipeng
Abstract: Bi metal attached BiOBr with oxygen defect (BiOBr(3)-Bi(x%, x = 10, 20, 30)) nanosheets was prepared via the hydrothermal process in this study. The different characterization techniques of x-ray diffraction, x-ray photoelectron spectrometer, electron spin resonance (ESR), field emission scanning electron microscope, and high resolution transmission electron microscope were used to distinguish the composition, crystal structure, and morphology of the samples. Under visible light irradiation, the BiOBr(3)-Bi(x%, x = 10, 20, 30) samples exhibited improved photocatalytic activity for the degradation of colored dyes (RhB) and colorless tetracycline hydrochloride. Such an improvement was ascribed to the widened visible light absorption and enhanced separation of the photogenerated electron–hole pairs because of the synergistic effect of oxygen vacancies and Bi metal with plasmon resonance effects. A possible photocatalytic mechanism of the quasi Z-scheme process was proposed on the basis of ESR measurements and radical-trapping experiments.